The Clinicopathologic and Prognostic Significance of Programmed Cell Death Ligand 1 (PD-L1) Expression in Patients With Prostate Cancer: A Systematic Review and Meta-Analysis - Li, Yan; Huang, Qingying; Zhou, Yaoyao; He, Meizhi; Chen, Jianhong; Gao, Yubo; Wang, Xue (Frontiers in Pharmacology, 2019)
Background: Programmed cell death ligand 1 (PD-L1) expression has been shown to correlate with poor prognosis in diverse human cancers. However, limited data exist on the prognostic and clinicopathologic significance of PD-L1 expression in prostate cancers (PCa), and the curative effect of anti-PD-1/PD-L1 therapy remains controversial. In this systematic review and meta-analysis, we aimed to evaluate the prognostic and clinicopathologic value of PD-L1 in PCa. Methods: We performed a systematic literature search in the PubMed, Cochrane Library, EMBASE, Web of Science, and SCOPUS databases up to July 21st 2018. Pooled prevalence of PD-L1 in PCa were calculated using Freeman-Tukey double arcsine transformation by R software version 3.5.0. The data from the studies were examined by a meta-analysis using Review Manager software 5.3 to calculate pooled hazard ratios (HRs) and pooled odds ratios (ORs) with their 95% confidence intervals (CIs) to estimate the prognostic and clinicopathologic value of PD-L1 in PCa, respectively. Heterogeneity was tested by the Chi-squared test and I2 statistic. Results: Five studies with 2,272 patients were finally included in this meta-analysis. The pooled prevalence of PD-L1 in PCa was 35% (95% CI 0.32 to 0.37). Both PD-L1 expression (HR=1.78; 95 % CI 1.39 to 2.27; p<0.00001) and PD-L1 DNA methylation (HR=2.23; 95% CI 1.51 to 3.29; p<0.0001) were significantly associated with poor biochemical recurrence-free survival (BCR-FS). PD-L1 tended to have high expression level in high Gleason score cases (OR=1.54; 95% CI, 1.17 to 2.03; P=0.002) and androgen receptor-positive cases (OR=2.42, 95% CI 1.31 to 4.50; P=0.005). However, PD-L1 had relatively weak correlation with age, pathologic stage, lymph node metastasis and preoperative PSA level. Conclusions: This meta-analysis confirms the negative prognostic significance of PD-L1 expression and mPD-L1 in PCa patients. And PD-L1 has a correlation with Gleason score and androgen receptor status with statistical significance, while the correlations with age, pathologic stage, lymph node metastasis and preoperative PSA level were not statistically significant. However, the number of included studies is too small to make the conclusions more convincing due to limited published studies, so more retrospective large-cohort studies are expected for the further confirmation of these findings.